2022
DOI: 10.1186/s12984-022-00990-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing effects of exoskeleton misalignment on knee joint load during swing using an instrumented leg simulator

Abstract: Background Exoskeletons are working in parallel to the human body and can support human movement by exerting forces through cuffs or straps. They are prone to misalignments caused by simplified joint mechanics and incorrect fit or positioning. Those misalignments are a common safety concern as they can cause undesired interaction forces. However, the exact mechanisms and effects of misalignments on the joint load are not yet known. The aim of this study was therefore to investigate the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
1
24
0
1
Order By: Relevance
“…The knee moves through two sets of flexion and extension in a normal gait cycle: the first occurs from initial loading to midstance, and the second occurs from pre-swing to the initial swing [ 18 , 25 ]. A few studies have suggested that some misalignments between the user’s anatomical and exoskeleton joints can cause undesired interaction forces, which in turn reduce comfort and safety [ 26 , 27 , 28 ]. Misalignments have been discussed as a potential cause for lower limb fractures for a powered exoskeleton use [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The knee moves through two sets of flexion and extension in a normal gait cycle: the first occurs from initial loading to midstance, and the second occurs from pre-swing to the initial swing [ 18 , 25 ]. A few studies have suggested that some misalignments between the user’s anatomical and exoskeleton joints can cause undesired interaction forces, which in turn reduce comfort and safety [ 26 , 27 , 28 ]. Misalignments have been discussed as a potential cause for lower limb fractures for a powered exoskeleton use [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bessler-Etten, et al [13] Investigating the effects of misalignment in different directions and rotationally to find if there is an increased load on the knee joint.…”
Section: Objective Findings Significance Limitationsmentioning
confidence: 99%
“…Kinematics of such systems are analyzed through different motion trajectories ( Figure 1 ) [ 12 ]. Although there are many related studies on moving the knee joint axis over various different subjects [ 13 , 14 , 15 , 16 ], it seems more research is required to develop a comprehensive insight through the sensitivity of exoskeleton design so as to provide a more reliable human-exoskeleton coordination. Table 1 presents a brief summary of similar studies, presenting their characteristics and limitations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the exoskeleton assisting the ankle would increase the distal inertia inevitably, and a load acting far from the centre of mass would significantly increase the metabolic consumption [53]. To avoid this disadvantage, exoskeletons assisting the knee joint [54][55][56] or the hip joint [12,[57][58][59] was developed which are shown in Figure 2(c) and (d). The primary function of the knee is to support the body weight both in the single-support and double-support phases, and to increase foot clearance, avoiding obstacles in the swing phase by bending [56].…”
Section: Exoskeletons Providing Joint Torquesmentioning
confidence: 99%